Prevalence and significance of bacterial contamination of autologous stem cell products. (August 2021) - Damonti, L.; Buetti, N.; Droz, S.; Bacher, U.; Pabst, T.; Taleghani, B.M.; Baerlocher, G.M.; Marschall, J.
Summary: There is limited and conflicting information on the prevalence of contamination of haematopoietic stem and progenitor cell products (HPCPs), and their optimal management remains unclear. The authors reviewed the microbial surveillance data of HPCPs collected between January 2002 and December 2019 for autologous transplantation at the study institution to determine the prevalence of microbial contamination and the potential infectious complications among recipients. Among 3935 HPCPs, 25 (0.6%) were contaminated. Ultimately, 22 patients received contaminated grafts, with pre-emptive antimicrobial therapy initiated in six of these patients. No patients developed subsequent infectious complications. These data suggest that microbial contamination of autologous HPCPs and associated adverse outcomes are rare.